2020
DOI: 10.3390/ma13102393
|View full text |Cite
|
Sign up to set email alerts
|

Octahydroquinoxalin-2(1H)-One-Based Aminophosphonic Acids and Their Derivatives—Biological Activity towards Cancer Cells

Abstract: In the search for new antitumor agents, aminophosphonic acids and their derivatives based on octahydroquinoxalin-2(1H)-one scaffold were obtained and their cytotoxic properties and a mechanism of action were evaluated. Phosphonic acid and phosphonate moieties increased the antiproliferative activity in comparison to phenolic Mannich bases previously reported. Most of the obtained compounds revealed a strong antiproliferative effect against leukemia cell line (MV-4-11) with simultaneous low cytotoxicity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…The phosphonic α-amino acids and their derivatives has a considerable role play in the design of new drugs [1]. Thus, these derivatives have a high potential for diverse biological activity [2], acting as a protease inhibitor agent of West Nile virus [3], anticancer agent [4], antibacterial [5], antioxidant [6].…”
Section: Introductionmentioning
confidence: 99%
“…The phosphonic α-amino acids and their derivatives has a considerable role play in the design of new drugs [1]. Thus, these derivatives have a high potential for diverse biological activity [2], acting as a protease inhibitor agent of West Nile virus [3], anticancer agent [4], antibacterial [5], antioxidant [6].…”
Section: Introductionmentioning
confidence: 99%
“…It can be expected that introduction of this functionality into a nitrogen heterocycle can result in a desired biological activity [ 16 ]. Indeed, our research proved that incorporation of phosphorus functionality greatly improves antiproliferative activity of N -heterocycles obtained by our group [ 17 ]. Cytotoxicity of the products were relatively low to normal cells making them promising compounds for drug development.…”
Section: Introductionmentioning
confidence: 79%
“…Significantly better results were obtained for two derivatives: a phosphonate bearing big TADDOL—derived moiety 4e , and a monocyclic diamine with trifluoromethyl substituent 6 . Compound 4e was previously tested in our previous antiproliferative study using other cancer lines and was found as the only active compound [ 17 ]. Moreover, a mixture of epimers which was obtained from the synthesis was even more efficient in comparison with a pure enantiomer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Les α-aminoacides phosphoniques et leurs dérivés occupent une place importante dans la conception de nouvelles formules de médicaments (Iwanejko et al, 2020). Ainsi, ces dérivés sont dotés d'un fort potentiel d'activité biologique intéressant et divers (Damiche et al, 2016), agissant comme agent inhibiteur de la protéase du virus Nil occidental (Skoreński et al,2019), agents anticancéreux (Fang et al, 2016), antibactériens (Tripolszky et al, 2020) et antioxydants (Nayab et al, 2020).…”
Section: Introductionunclassified